USAHA MENINGKATKAN AKTIVITAS BELAJAR SISWA PADA PEMBELAJARAN KOMPUTER AKUNTANSI DENGAN BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI DI KELAS 2 AKUNTANSI 2 SMKN 1 SOLOK - Zuhilmi Zuhilmi (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2017)
This research aimed to describe the activities of students in computer learning accounting accounting class 2 2 SMK Solok based on information technology and communications. This research is a class action research. Subjects of research is students in grade 2 Accounting I SMK 1 Solok learning year 2009/2010 in the third semester, the following study accounting computer as many as 33 students. The object of research is computer lessons accounting are included in a group of subjects productively (accounting expertise package) with the competence of the accounting cycle services company working with the computer through the MYOB accounting program. The results of this study is the use of media-based learning information and communication technology in learning accounting computer can increase the activity of students and also practice at the laboratory computer activity also increased, averaging more than 95% of students work diligently in the tasks given, students have high interest to repeat the steps and accounting procedures that have been described.